Subtrochanteric Osteotomy in Direct Anterior Approach Total Hip Arthroplasty - Liu, Zai‐yang (Orthop Surg, 2020)
Subtrochanteric osteotomy of the femur (STO) is a valuable corrective procedure in hip surgeries. However, STO in traditional posterolateral approach usually encounters complications such as postoperative dislocation, bone non‐union, and prosthesis failure. Some relevant pathologies and mechanisms have been identified, but there is sparse evidence for verification. The aim of this video in orthopaedic technique is to test our hypothesis of STO in direct anterior approach to total hip arthroplasty in a complicated hip surgery, and to further illustrate the rationality, reproducibility, and superiority of STO in this minimally invasive and enhanced‐recovery approach by presenting a standardized and systemic protocol, as well as operational pearls and pitfalls.